Sistem Pakar Diagnosa Penyakit Tanaman Tomat yang Disebabkan Abu Vulkanik Sinabung Menerapkan Metode Teorema Bayes - Suriyani Br Kudadiri; Nelly Astuti Hasibuan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Mount Sinabung is an active mountain located in Karo District, North Sumatra. Mount Sinabung is the highest peak in the province of North Sumatra with an altitude of 2451 MDPL. The eruption of Mount Sinabung on the Karo soil made every village exposed to volcanic ash, and not only that, the existing plants in the area became damaged and made farmers fail to harvest. The tomato plants in the area around Mount Sinabung were damaged due to volcanic ash bursts, as a result the tomatoes failed to harvest and suffered losses. From the volcanic ash bursts, the tomatoes were damaged due to volcanic ash. Expert system is a system that uses human knowledge where this knowledge is entered into a computer and then used to solve problems that usually require human expertise or expertise. In probability theory and statistics, the Bayes theorem is a theorem with two different interpretations. In Bayes' interpretation, this theorem states how far the degree of subjective belief should change rationally when there are new clues. The Bayes theorem method is a good method in machine learning based on training data, using conditional probability as its basis.